PENGARUH MANAJEMEN KELAS DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR - Agus Yuniar; Ahmad Syafii (Lembaga Pendidikan dan Pelatihan Sindotech, 2023)
Management in each school varies according to the characteristic conditions of its students. The atmosphere, environment and layout of the school certainly affect the existence of its students. The success of learners is influenced by several factors. The purpose of this study is to find out what factors affect the learning outcomes of students. The subjects of this study were 20 teachers and 60 students in grade 7 of SMP Negeri 6 Sidoarjo Regency. This type of research uses field research with a quantitative approach. The data collection method uses questionnaires using statistical analysis through the help of SPSS. The results of this study found that classroom management affects student learning outcomes with similarities of 18.4% while school environmental conditions affect student learning outcomes by 12.7% and classroom management and school environment affect by 22% Therefore, student learning outcomes at SMPN 6 Sidoarjo can be determined by good and bad classroom management and school environment.